Geochemical Fractionation of Trace Elements in Stream Sediments Contaminated by Mining Activity. Issue 3 (30th June 2014) - Favas, Paulo J. C.; Sarkar, Santosh Kumar; Rakshit, Dibyendu
<x xml:space="preserve">Abstract</x> This study was conducted along the watercourses which drain an abandoned mine (Vale das Gatas mine, Northern Portugal) with an objective to identify and quantify the impact of the mining activity on the quality of specific stream sediment fractions. The first phase of the study detected anomalous "total" concentrations of trace elements in the following sequential order: 9000 mg/kg Zn > 8200 mg/kg Pb > 5900 mg/kg W > 2450 mg/kg As > 1100 mg/kg Cu. The index of geoaccumulation values indicate that the sediment in the mine area and downstream the tailings were unpolluted to moderately polluted with Zn, unpolluted to highly polluted with Cd, moderately to highly polluted with Cu, moderately to very highly polluted with Pb and highly to very highly polluted with As. Some samples of stream sediments were selected for application of a modified sequential extraction technique to investigate the chemical elements present in the geochemical fractions of the sediment, thus identifying their toxicity, mobility, and degree of availability to the aquatic environment. Despite high total concentrations of several elements (Zn, Pb, W, As, Mn, Cu, Cd), only Pb and As are likely to create a dangerous situation according to the risk assessment code.